Inflation differentials in a Monetary Union: the case of Malta - Brian Micallef; Laurent Cyrus (Central Bank of Malta, 2013)
The objective of this paper is to enhance the understanding of inflation dynamics in Malta and investigate the underlying sources of inflation differentials with the euro area. A country that registers persistently higher inflation than its main trading partners will suffer from a deterioration in its external price competitiveness, with subsequent losses in output and employment. This is even more relevant in the context of a monetary union, where asymmetric shocks cannot be corrected by changes in monetary or exchange rate policies but rather through structural policies and relative adjustments in prices and wages.
Keywords: 330